ChemInform Abstract: Recent Advances in the Chemistry of Organic Thiocyanates. Issue 13 (March 2016) - Castanheiro, Thomas; Suffert, Jean; Donnard, Morgan; Gulea, Mihaela
Abstract: Review: [different methods for the preparation of organic thiocyanates and their synthetic applications; 50 refs.